Análisis de la normatividad de contaminación auditiva de los autódromos a partir del estudio de caso del autódromo XRP (2018)
According to the Cajicá Territorial Ordinance Plan, the area of the XRP Motorpark belongs to the category of recreational and institutional zone. For some years, XRP Motorpark has faced problems related to the noise levels produced by its sports and cultural activities; thus, in 2010, a popular ac-tion was presented which aimed to suspend the sports activities of the autodrome due to the high levels of noise produced in the competitions of motor vehicles and motorcycles to combustion. This article presents a diagnosis about the regulations that are applied to regulate the noise emis-sions produced by the sports and cultural activities of the autodrome that exceed the decibel level allowed. For this, in the first instance, the laws, resolutions and international decrees concerning the control and reduction of auditory contamination and the impact on health and the environment are reviewed. Subsequently, the current problem of the Cajicá autodrome with respect to Colombian regulations is identified. Finally, a solution is proposed so that the XRP Motopark of Cajicá can adapt or seek some type of modification of the noise emission regulations in order to continue with its normal activities, without canceling events or being sanctioned for non-compliance.